Perturbed CD8+ T cell immunity across universal influenza epitopes in the elderly. Issue 2 (29th December 2017) - Nguyen, Thi H O; Sant, Sneha; Bird, Nicola L; Grant, Emma J; Clemens, E Bridie; Koutsakos, Marios; Valkenburg, Sophie A; Gras, Stephanie; Lappas, Martha; Jaworowski, Anthony; Crowe, Jane; Loh, Liyen; et al.
Abstract: Influenza epidemics lead to severe illness, life-threatening complications, and deaths, especially in the elderly. As CD8 + T cells are associated with rapid recovery from influenza, we investigated the effects of aging on antigen-specific CD8 + T cells across the universal influenza epitopes in humans. We show that aging is characterized by altered frequencies in T cell subsets, with naive T cells being partially replaced by activated effector/memory populations. Although we observed no striking differences in TCR signaling capacity, T cells in the elderly had increased expression of transcription factors Eomes and T-bet, and such changes were most apparent in CD8 + T cells. Strikingly, the numbers of antigen-specific CD8 + T cells across universal influenza epitopes were reduced in the elderly, although their effector/memory phenotypes remained stable. To understand whether diminished numbers of influenza-specific CD8 + T cells in the elderly resulted from alteration in TCR clonotypes, we dissected the TCRαβ repertoire specific for the prominent HLA-A*02:01-restricted-M158–66 (A2/M158 ) influenza epitope. We provide the first ex vivo data on paired antigen-specific TCRαβ clonotypes in the elderly, showing that influenza-specific A2/M158 + TCRαβ repertoires in the elderly adults varied from those in younger adults, with the main features being a reduction in the frequency of the public TRAV27–TRBV19 TCRαβ clonotype, increased proportion of private TCRαβ signatures, broader use of TRAV and TRBV gene segments, and large clonal expansion of private TCRαβ clonotypes with longer CDR3 loops. Our study supports the development of T cell-targeted influenza vaccines that would boost the T cell compartment during life and maintain the numbers and optimal TCRαβ signatures in the elderly.